Cost-benefit analysis of cycle to work scheme - Gradin, Sandra (2019)
In a response to negative externalities such as GHG emission, health costs, infrastructural costs, noise and air pollution etc. caused by motorised transportation international organizations and governments have started promoting shifts towards active transportation such as walking and cycling. This study use a CBA-framework to evaluate a cycle to work- scheme implemented in Jönköping municipality in 2016. The scheme allowed all municipality employees to lease bicycles or e-bikes for a three year period and pay for them through a salary sacrificing arrangements, after the three year were over the participants could either buy the vehicle at market value or return it free of charge. Eleven parameters were included in the CBA, the internalisation through taxation/fees of some of the effect for some parameters were taken into consideration as well as the shorter Swedish bicycle season (31 weeks on average). The result indicate a benefit-cost ratio of 6.21:1, meaning that C2W scheme is a cost efficient method of increasing AT usage.